An historical survey of the botanical research done at the Lousã mountain system (Portugal) - Rodrigues, Sónia Sofia S.; Ferreira, Carla Sofia S.; Silveira, Paulo C. (Botanica Complutensis, 2005)
This work is intended to be the first contribution to a checklist of the vascular plant flora of the Lousã mountain system. Only bibliographic records are included, specially the ones extracted from studies dating from the 19th century, for a future comparison with the present diversity. A total of 225 taxa where recorded, of which at least 86 % can still actually be found in the study area, according with our field observations. However, at least four are most probably extinct, because no population are actually known.